Control interno basado en coso i y su incidencia en los proyectos agrícolas que promueve el gobierno a la corporación agrícola ganadera río Mocache en el año 2022. - Triana García , Ana Isabel (2024)
This research project was carried out in the Mocache Canton, Los Ríos Province, with the objective of evaluating the internal control based on COSO I and its impact on the Agricultural Projects promoted by the Government to the Río Mocache Livestock Agricultural Corporation in the year 2022. The study was based on the application of the components of COSO I, through an interview with the secretariat, which revealed inefficiencies in management policies, with a low confidence level of 32% and a high inherent risk of 68%, due to the lack of policies and procedure manuals. Furthermore, an internal control questionnaire addressed to the president showed that internal control was unproductive, with a low confidence level of 38% and a high inherent risk of 62%, due to the lack of transparency, non-compliance in its projects and the poor administrative management. Indicators were also applied, obtaining results of efficiency of 19%, effectiveness of 42% and effectiveness of 25%. According to the findings, it was determined that the gaps in all indicators were unfavorable, due to the lack of efficient internal control that allows preventing and detecting risks. It was proven that there is poor planning, poor communication and supervision in all processes and controls. To solve this problem, internal processes must be improved, calculating the current internal control regulations that are applicable, ensuring the efficiency and effectiveness of Agricultural projects, contributing to the fulfillment of the Corporation's organizational objectives